RELATIONSHIP OF RESPONSE TIME AGAINST ACCURACY IN EMPLOYEE ACTIVITIES INPATIENT CARDIAC ARREST - lutfi wahyuni; agus Haryanto (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2019)
Cardiac arrest is a condition where the heart is unable to pump blood at all as a result of abnormal heart rhythms that are not effective. Response time is the speed and accuracy of service time needed by patients to get help in accordance with the emergency of the disease since entering the emergency room. Good response time for patients is <5 minutes if it passes it can result in the lives of patients in danger and can even cause death. The purpose of this study is to determine the relationship of response time to the emergency actions of cardiac arrest patients. The design in this study was an analytical correlation using a cross-sectional approach. The population in this study were all nurses in the IGD and ICU in Sakinah Mojokerto Hospital and Hasanah Mojokerto Hospital in 52 nurses. The sampling technique used is total sampling. The instrument used was a stopwatch and SOP observation sheet for handling Cardiac arrest patients. The results showed that most nurses had response time ≤ 5 minutes as many as 35 respondents (67.3%) and the accuracy of emergency actions in cardiac arrest patients according to SOP were 40 respondents (76, 9%). The faster the nurse performs the response time it is expected that the more appropriate in performing emergency actions in cardiac arrest patients